1979
DOI: 10.1099/00221287-110-1-21
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Enzymes Produced by Ruminococcus flavefaciens which Degrade Plant Cell Walls

Abstract: Enzyme preparations active against crystalline cellulose, marble-milled filter paper, carboxymethylcellulose (CM-cellulose), hemicellulose and xylan were obtained from cultures of Ruminococcus jlavefaciens. These preparations also contained swelling factor, pectin methylesterase, pectin lyase and low levels of aryl P-glucosidase and aryl P-xylosidase. CM-cellulase and xylanase activities were present in a high molecular weight complex, but substrate competition studies showed that different active sites were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
1
1

Year Published

1979
1979
2000
2000

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(67 citation statements)
references
References 16 publications
6
59
1
1
Order By: Relevance
“…This finding is in agreement with results of previous studies, which indicated that, in other cellulolytic bacteria, the above-mentioned activities are present within a single protein complex (9,20,23). The different temperature and pH optima for Avicelase, CMCase, and xylanase activities in the 700,000-Mr protein complex of strain C7 suggest that different enzymatically active components within the complex are responsible for the hydrolysis of these substrates.…”
Section: Discussionsupporting
confidence: 82%
“…This finding is in agreement with results of previous studies, which indicated that, in other cellulolytic bacteria, the above-mentioned activities are present within a single protein complex (9,20,23). The different temperature and pH optima for Avicelase, CMCase, and xylanase activities in the 700,000-Mr protein complex of strain C7 suggest that different enzymatically active components within the complex are responsible for the hydrolysis of these substrates.…”
Section: Discussionsupporting
confidence: 82%
“…The nature and Sources of the celluloses, hemicelluloses and pectin are listed by Pettipher & Latham (1979). Growth on larchwood xylan and oak sapwood hemicellulose was assessed by measuring the disappearance of carbohydrate (Dubois et al, 1956) and by the increase in total cell numbers.…”
Section: Methodsmentioning
confidence: 99%
“…Ruminococcus flavefaciens strains 67 and 66 (Latham et al, 1978) and the type strain c94 (from Dr M. P, Bryant, Department of Dairy Science, University of Illinois, U.S.A.) were cultivated in basal medium. BMlO containing 0.1 yo (w/v) cellobiose (Pettipher & Latham, 1979). Methods of strict anaerobic culture (Bryant, 1972) were used throughout and all cultures were incubated at 39 "C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations